2009
DOI: 10.1037/a0017655
|View full text |Cite
|
Sign up to set email alerts
|

Transplantation of hippocampal cell lines restore spatial learning in rats with ventral subicular lesions.

Abstract: We have demonstrated in our previous studies that ventral subicular lesion induces neurodegeneration of the hippocampus and produces cognitive impairment in rats. In the present study, the efficacy of transplanted green fluorescent protein (GFP)-labeled hippocampal cell line (H3-GFP) cells in establishing functional recovery in ventral subicular lesioned rats has been evaluated. The survival of H3-GFP transplants and their ability to express trophic factors in vivo were also investigated. Adult male Wistar rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 70 publications
2
12
0
Order By: Relevance
“…In contrast, these behavioral deficits were completely ameliorated in hippocampaldamaged mice that received intravenous injections of HEK cells or HEK-CM. This observation is consistent with the previous reports that cell therapies could ameliorate behavioral deficits in animal models of hippocampal neurodegeneration [6,7]. However, the current study is the first of its kind to demonstrate that infusion of HEK-CM per se could effectively ameliorate co-morbidities that are commonly observed in hippocampal-impaired subjects.…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In contrast, these behavioral deficits were completely ameliorated in hippocampaldamaged mice that received intravenous injections of HEK cells or HEK-CM. This observation is consistent with the previous reports that cell therapies could ameliorate behavioral deficits in animal models of hippocampal neurodegeneration [6,7]. However, the current study is the first of its kind to demonstrate that infusion of HEK-CM per se could effectively ameliorate co-morbidities that are commonly observed in hippocampal-impaired subjects.…”
Section: Discussionsupporting
confidence: 94%
“…Hippocampal damage also leads to mood instability such as depression, which in turn affects an individual's day-to-day life severely [26]. Several studies have shown the beneficial effects of cell therapies in ameliorating hippocampal cell death and behavioral abnormalities in animal models of hippocampal degeneration [6,7]. In the present study, behavioral deficits were readily identifiable in hippocampal damaged mice because these mice were unable to discriminate between familiar and novel objects, and these mice displayed severe depressionlike symptoms.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Thus, there is a pressing need to identify alternative therapeutic strategies to arrest the progression of neurodegeneration. Cell therapy is emerging as a potential therapeutic modality against neurodegenerative diseases (Li et al ., , ; Maisano et al ., ; Rekha et al ., ). Two possible avenues through which functional recovery could be achieved include stimulation, followed by mobilization of endogenous stem cells towards the vicinity of degenerating sites (Diederich et al ., ; Li et al ., ; Sehara et al ., ), or transplanting exogenous neural cells that can proliferate and replace the lost neurons (Maisano et al ., 2009; Rekha et al ., , ).…”
Section: Cell‐based Therapies For Combating Neurodegenerative Diseasesmentioning
confidence: 97%
“…Cell therapy is emerging as a potential therapeutic modality against neurodegenerative diseases (Li et al ., , ; Maisano et al ., ; Rekha et al ., ). Two possible avenues through which functional recovery could be achieved include stimulation, followed by mobilization of endogenous stem cells towards the vicinity of degenerating sites (Diederich et al ., ; Li et al ., ; Sehara et al ., ), or transplanting exogenous neural cells that can proliferate and replace the lost neurons (Maisano et al ., 2009; Rekha et al ., , ). The concept of adult neurogenesis is now widely acknowledged and is known to occur in two brain regions, the subventricular zone (SVZ) and the subgranular zone (SGZ) of the DG (Deng et al ., ; Li et al ., ; Suh et al ., ; Thuret et al ., ; van Praag et al ., ).…”
Section: Cell‐based Therapies For Combating Neurodegenerative Diseasesmentioning
confidence: 97%